Integrating ecological and economic modeling of eutrophication: toward optimal solutions for a coastal area suffering from sediment release of phosphorus - Laukkanen, Marita; Ekholm, Petri; Huhtala, Anni; Pitkänen, Heikki; Kiirikki, Mikko; Rantanen, Pirjo; Inkala, Arto (Royal Swedish Academy of Sciences, 2009)
This paper puts forward a model for managing eutrophication that integrates the salient ecological and economic characteristics of a coastal area suffering from severe nutrient enrichment. The model links the development of phosphorus concentration over time to nutrient emissions from agriculture and habitation. It accounts for differences in agricultural and municipal abatement options and their costs, as well as the need to undertake irreversible investments to set up wastewater treatment facilities. Furthermore, it considers sediment release of phosphorus as a function of annual nutrient loads. The model is parameterized for a 30-km-wide area off the Finnish coast of the Gulf of Finland. The socially optimal policy, which minimizes the sum of monetary damage caused by eutrophication and the costs of nutrient abatement over time, is determined using a dynamic programming approach. The results suggest that considerable investments are warranted to bring wastewater treatment facilities up to date. Continued efforts to reduce agricultural nutrient loading are nevertheless also called for. The analysis provided is a first step toward an integrated analysis of eutrophication that accounts for complexities inherent in the problem, such as sediment release of phosphorus and irreversible investments in abatement technology. The results are sensitive in particular to ecological assumptions and parameterization, and further research is needed in these areas.
Keywords: Ma; rehevöityminen; rannikkoalueet; fosfori; ravinteet; rikastuminen; jätevedenkäsittely; eutrophication; coastal areas; phosphorus; nutrients; wastewater treatment; nutrien enrichment